Cryptosporidium equi n. sp. (Apicomplexa: Cryptosporidiidae): Biological and genetic characterisations - Huang, Jianbo; Chen, Ming; He, Yongli; Chen, Haoyu; Huang, Mingming; Li, Na; Ryan, Una; Kváč, Martin; Feng, Yaoyu; Xiao, Lihua; Guo, Yaqiong (International journal for parasitology, 2023)
The horse genotype is one of three common Cryptosporidium spp. in equine animals and has been identified in some human cases. The species status of Cryptosporidium horse genotype remains unclear due to the lack of extensive morphological, biological, and genetic data. In the present study, we have conducted biological and whole genome sequence analyses of an isolate of the genotype from hedgehogs and proposed to name it Cryptosporidium equi n. sp. to reflect its common occurrence in equine animals. Oocysts of C. equi measured 5.12 ± 0.36 μm × 4.46 ± 0.21 μm with a shape index of 1.15 ± 0.08 (n = 50). Cryptosporidium equi was infectious to 3-week-old four-toed hedgehogs (Atelerix albiventris) and mice, with a prepatent period of 2-9 days and a patent period of 30-40 days in hedgehogs. It was not infectious to rats and rabbits. Phylogenetic analyses of small subunit rRNA, 70 kDa heat shock protein, actin, 60 kDa glycoprotein and 100 other orthologous genes revealed that C. equi is genetically distinct from other known Cryptosporidium species and genotypes. The sequence identity between C. equi and Cryptosporidium parvum genomes is 97.9%. Compared with C. parvum, C. equi has lost two MEDLE genes and one insulinase-like protease gene and gained one SKSR gene. In addition, 60 genes have highly divergent sequences (sequence differences ≥ 5.0%), including those encoding mucin-like glycoproteins, insulinase-like peptidases, and MEDLE and SKSR proteins. The genetic uniqueness of C. equi supports its increasing host range and the naming of it as a valid Cryptosporidium species. This is the first known use of whole genome sequence data in delineating new Cryptosporidium species.
Keywords: Taxonomy; feces; Humans; Cryptosporidiosis; Phylogeny; kryptosporidióza; Cryptosporidium horse genotype; Horses; insulinasa; krysa rodu Rattus; Cryptosporidium; lidé; Genotype; koně; zvířata; myši; Cryptosporidium equi; Mice; Feces; New species; Comparative genomics; fylogeneze; králíci; Rats; genotyp; Animals; Cryptosporidiidae; Hedgehogs; Insulysin; Rabbits; ježkovití